TO THE PROBLEM OF DEVELOPMENT OF PERFORMANCE SKILLS FUTURE MUSIC TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
In article problems, of development of performing skills of the future musicians - teachers are considered. Classification is submitted and concrete performing skills, which are necessary for forming in the higher school, are determined.